"Le public est prié de ne pas se méprendre …": le double sens grivois dans les Comédies et Proverbes d'Alfred de Musset. Issue 3 (December 2018) - Castagnès, Gilles
Abstract : Musset's eroticism has been the object of much critical study, especially in relation to his narrative and poetic works. Critics have shown the writer's passionate, even morbid sense of sexuality. The aim of this article, which focuses on Comédies et Proverbes, is to decipher the double entendres hidden in his theatre. It attempts to identify the situations in which these double entendres are most likely to appear, and the original effects produced by this feature of Musset's theatre. Engaging not only the reader but also the audience, the Comédies et Proverbes contain a playful form of eroticism, at variance with its serious and fatal aspects.